2020
DOI: 10.24252/asma.v2i2.17084
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Kartu Kuartet Sebagai Media Pembelajaran Biologi

Abstract: Tujuan penelitian ini yaitu untuk mengembangkan media pembelajaran biologi kartu kuartet yang valid, praktis, dan efektif. Jenis penelitian ini adalah penelitian pengembangan. Model pengembangan yang digunakan adalah model 4-D Thiagarajan (Define, Design, Develop, dan Disseminate). Subjek penelitiannya adalah peserta didik kelas XI MA As-Shalihin Gowa, pada semester genap tahun ajaran 2019/2020. Instrumen penelitian yang digunakan adalah lembar validasi, angket respons, dan tes hasil belajar peserta didik. Tek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…These findings align with the outcomes of prior research, such as Giwangsa's (2021) study titled "Card Media Improvement in Primary School Social Examinations Learning" , where students' responses exceeded 90%, categorizing the media as "highly practical." This reinforces the notion that card media can serve as an invaluable learning resource in schools, as indicated in the study conducted by Ismail et al (2020). Furthermore, Izza's (2018) research, titled "Development of card learning media on cultural diversity in Indonesia class IV MINU Raudlatul Falah Talok Malang" , supports the idea that KAPIN material has the potential to enhance students' reading abilities.…”
Section: Evaluation Stagesupporting
confidence: 65%
“…These findings align with the outcomes of prior research, such as Giwangsa's (2021) study titled "Card Media Improvement in Primary School Social Examinations Learning" , where students' responses exceeded 90%, categorizing the media as "highly practical." This reinforces the notion that card media can serve as an invaluable learning resource in schools, as indicated in the study conducted by Ismail et al (2020). Furthermore, Izza's (2018) research, titled "Development of card learning media on cultural diversity in Indonesia class IV MINU Raudlatul Falah Talok Malang" , supports the idea that KAPIN material has the potential to enhance students' reading abilities.…”
Section: Evaluation Stagesupporting
confidence: 65%
“…Jika dibandingkan pada penelitian sebelumnya sudah banyak pengembangan media ajar untuk pelajaran biologi yang menggunakan kartu. Diantaranya berupa permainan yang terdiri dari kartu soal dan jawaban (Hadiyanti, 2021), kartu kuartet (Ismail, Taufiq, & Hasanah, 2020), kartu indeks (Thahir, 2020), dan kartu pada materi protista dengan sistem permainan seperti UNO (Aulya, Zulyusri, & Rahmawati, 2021). Tetapi semua itu berbeda dengan konsep kartu yang ditawarkan pada Kartu Semesta ini.…”
Section: Hasil Dan Pembahasanunclassified
“…Quarter-card games are commonly referred to as cards that describe one of the games used in learning. The game is fun, this game is also not alien to its existence to students, the material used in this quartet card can be accompanied by descriptions according to the picture, so it can stimulate the desire of children to learn it (Ismail et al, 2020). Modified quartet cards not only help improve a child's knowledge but are also used to improve behavior.…”
Section: Influence Of Quartet Card Games On Reproductive Health On Kn...mentioning
confidence: 99%
“…Several research results at various levels of education revealed that the media of quartet card games positively influenced the attitude and knowledge of students in receiving lessons (Ismail et al, 2020). Quartet media is also able to enhance students' skills in conducting group collaboration, helping each other in learning, and creating enjoyable learning situations.…”
Section: Introductionmentioning
confidence: 99%